Meta analysis of pathogenic airborne bacteria at nurseries and day care centres - Zakaria Hamid; Ahmad Umar Qayyum Bin Abdul Aziz; Pang Jyh Chyang (LPPM Universitas Duta Bangsa Surakarta, 2022)
There are currently no specific rules and regulation on what the limit for the bacterial concentration at nurseries and day care centres. Being exposed to bioaerosols have become a health concern to the public especially children. This is because they spend most of their childhood in nurseries, day care centres and schools. Statistical analysis is done by Cochrane Software Review Manager 5.4. Based on the statistical analysis, the result of the included studies shows that the concentration of bacteria at nurseries and day care centres are significant. In recent studies, the values for indoor concentration ranged from the 510 CFU/m-3 until 52560 CFU/m-3. The most common types of bacteria that were found in the studies are Staphylococcus, Micrococcus, Bacillus, and Pseudomonas. In general, the studies noted that the bacteria were mostly non-pathogenic and do not pose an immediate danger to the children’s health. However, children who are immunodeficient are at a risk of infection and catching a disease and possibly serious health effects.